IMPLEMENTASI PERAMALAN PRODUKSI DI PT X DENGAN MENGGUNAKAN GREY METHOD - Rendiyatna Ferdian; Asep Anwar; Tiaradia Ihsan (LPPM Universitas Bina Bangsa, 2023)
The stages of a good production process begin with carrying out production planning and forecasting. This stage is carried out to reduce the impact of uncertainty in the future. There are many methods that can be used in forecasting, but there are often obstacles to the lack of data owned to do forecasting. Gray system theory is one of the theories developed to reduce the problem of lack data owned. This research tries to forecast the needs of PT X using the grey method. Based on the results of forecasting using the Grey Method, the method can produce forecasting with a good level of accuracy and is on the criteria of